2022
DOI: 10.1101/2022.05.18.492488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for different greater-persistence strategies under lower and higher challenge for alcohol in female rats

Abstract: Problem alcohol drinking is a substantial social and economic burden. Studies show that the misuse of alcohol is increasing in women, and that women can face higher consequences from alcohol exposure, but females have historically been understudied. Thus, there is considerable interest in understanding potential sex-different and -similar cognitive/emotional strategies, and underlying mechanisms, for alcohol responding, which would inform more effective, personalized treatments. Here, we used large cohorts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 108 publications
(214 reference statements)
0
1
0
Order By: Relevance
“…This study has some limitations, first we only used male rats. Another recent study from our laboratory showed that males and females have different strategies on CLAD intake, with females being more persistent than males for high challenges of quinine intake (De Oliveira Sergio et al, biorvix) thus, it would be of value to investigate the effect of these compounds in females. However, despite these limitations the present findings provide new insights to ongoing clinical studies about the effect of the β AR antagonist propranolol on CLAD and mainly the advantage of using lowest doses of propranolol and prazosin in combination as a pharmacological strategy for AUD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This study has some limitations, first we only used male rats. Another recent study from our laboratory showed that males and females have different strategies on CLAD intake, with females being more persistent than males for high challenges of quinine intake (De Oliveira Sergio et al, biorvix) thus, it would be of value to investigate the effect of these compounds in females. However, despite these limitations the present findings provide new insights to ongoing clinical studies about the effect of the β AR antagonist propranolol on CLAD and mainly the advantage of using lowest doses of propranolol and prazosin in combination as a pharmacological strategy for AUD treatment.…”
Section: Discussionmentioning
confidence: 99%